Cinema Africa 2023 - A conversation with Paméla Diop (in French) (A Conversation with ..., 2023)
Filmmaker and producer Paméla Diop was guest of the Africa Multiple Cluster of Excellence as part of the film festival Cinema Africa 2023 in Bayreuth. She presented her movie "Saloum" a Western type thriller set in the Senegalese region of the the same name. In this interview Paméla Diop talks with Marie Tsogo and Thierry Boudjekeu about making "Saloum" in particular and the process of African filmmaking in a more general sense.